Predicting the probability of long-term unemployment and recalibrating Ireland's statistical profiling model - Séamus McGuinness; Paul Redmond; Elish Kelly; Konstantina Maragkou (The Economic and Social Research Institute (ESRI), 2022)
Ireland's Probability of Exit (PEX) statistical profiling model predicts the likelihood that a claimant will still be unemployed 12 months after the day that they make their initial unemployment benefit claim. The model was initially developed by the Economic and Social Research Institute (ESRI) in 2009. At that time, the ESRI highlighted that the development of a statistical profiling tool was not a once-off procedure but that continuous assessment and updating of the model were required in order to maintain and improve its accuracy levels. In 2021, the Department of Social Protection (DSP) commissioned the ESRI to recalibrate the PEX model. The researchers were also tasked with identifying the key characteristics used in the model to determine a claimant's risk of becoming long-term unemployed while, at the same time, retaining model accuracy.
Keywords: 330